Strengths and Failure Characteristics of Self-Compacting Concrete Containing Recycled Waste Glass Aggregate - Rahman Khaleel AL-Bawi; Ihsan Taha Kadhim; Osamah AL-Kerttani (Advances in Materials Science and Engineering)
The effects of different proportions of green-colored waste glass (WG) cullet on the mechanical and fracture properties of self-compacting concrete (SCC) were experimentally investigated. Waste bottles were collected, washed, crushed, and sieved to prepare the cullet used in this study. Cullet was incorporated at different percentages (0%, 20%, 40%, 60%, 80%, and 100% by weight) instead of natural fine aggregate (NFA) and/or natural coarse aggregate (NCA). Three SCC series were designed with a constant slump flow of 700±30 mm, total binder content of 570 kg/m3 and at water-to-binder (w/b) ratio of 0.35. Moreover, fly ash (FA) was used in concrete mixtures at 20% of total binder content. Mechanical aspects such as compressive, splitting tensile, and net flexural strengths and modulus of elasticity of SCC were investigated and experimentally computed at 28 days of age. Moreover, failure characteristics of the concretes were also monitored via three-point bending test on the notched beams. The findings revealed that the mechanical properties as well as fracture parameters were adversely influenced by incorporating of WG cullet. However, highest reduction of compressive strength did not exceed 43% recorded at 100% WG replacement level. Concretes containing WG showed less brittle behavior than reference concrete at any content.